Light-based 3D bioprinting techniques for illuminating the advances of vascular tissue engineering - Wei Li; Jinhua Li; Chen Pan; Jae-Seong Lee; Byoung Soo Kim; Ge Gao (Materials Today Bio)
Vascular tissue engineering faces significant challenges in creating in vitro vascular disease models, implantable vascular grafts, and vascularized tissue/organ constructs due to limitations in manufacturing precision, structural complexity, replicating the composited architecture, and mimicking the mechanical properties of natural vessels. Light-based 3D bioprinting, leveraging the unique advantages of light including high resolution, rapid curing, multi-material adaptability, and tunable photochemistry, offers transformative solutions to these obstacles. With the emergence of diverse light-based 3D bioprinting techniques and innovative strategies, the advances in vascular tissue engineering have been significantly accelerated. This review provides an overview of the human vascular system and its physiological functions, followed by an in-depth discussion of advancements in light-based 3D bioprinting, including light-dominated and light-assisted techniques. We explore the application of these technologies in vascular tissue engineering for creating in vitro vascular disease models recapitulating key pathological features, implantable blood vessel grafts, and tissue analogs with the integration of capillary-like vasculatures. Finally, we provide readers with insights into the future perspectives of light-based 3D bioprinting to revolutionize vascular tissue engineering.